The effect of artificial anal band on quality of life of patients with fecal incontinence - (:unkn) unknown (My University, 2019)
Aim: The aim of this study was to evaluate incontinence levels before and after implantation of an artificial anal band (AAB), and toevaluate the change in quality of life of patients with fecal incontinence.Material and Methods: Patients with fecal incontinence who underwent AAB implantation were included in the study. The CleavelandClinic/Wexner Incontinence Score (CCIS) and Fecal Incontinence Quality of Life (FIQoL) scales were evaluated before, 2 weeks and5 years post-implantation.Results: Eight patients underwent AAB implantation. The mean±SD pre-operative CCIS decreased significantly (p<0.001) from19.4±0.5 to 3.1±0.6 two weeks after AAB activation. Similarly, a significant improvement was observed between mean pre- andpost-operative FIQoL scores (49.4 vs. 102.0; p=0.012). Most (62.5%) of the patients could actively use the implant. Surgical revisionwas performed in the post-operative period in 50% of the patients (n=4, 3 women). In 2 (25%) patients, AAB was explanted either dueto a secondary surgical site infection (n=1, man) or due to a perianal skin maceration (n=1, man).Conclusion: AAB implantation is an effective treatment option for improving quality of life in patients with fecal incontinence.Appropriate patient selection criteria may improve explantation and surgical revision rates and increase the rate of effective use ofAAB.
Keywords: Biyoloji; Diş Hekimliği; Alerji; Anatomi ve Morfoloji; Androloji; Anestezi; Odyoloji ve Konuşma-Dil Patolojisi; Biyokimya ve Moleküler Biyoloji; Biyofizik; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Kalp ve Kalp Damar Sistemi; Hücre Biyolojisi; Klinik Nöroloji; Yoğun Bakım, Tıp; Dermatoloji; Acil Tıp; Endokrinoloji ve Metabolizma; Gastroenteroloji ve Hepatoloji; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri; Hematoloji; İmmünoloji; Enfeksiyon Hastalıkları; Tamamlayıcı ve Entegre Tıp; Tıbbi Etik; Tıbbi İnformatik; Tıbbi Laboratuar Teknolojisi; Genel ve Dahili Tıp; Adli Tıp; Tıbbi Araştırmalar Deneysel; Mikrobiyoloji; Nörolojik Bilimler; Kadın Hastalıkları ve Doğum; Onkoloji; Göz Hastalıkları; Ortopedi; Kulak, Burun, Boğaz; Patoloji; Pediatri; Periferik Damar Hastalıkları; Fizyoloji; Temel Sağlık Hizmetleri; Psikiyatri; Halk ve Çevre Sağlığı; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Rehabilitasyon; Solunum Sistemi; Romatoloji; Spor Bilimleri; Cerrahi; Transplantasyon; Tropik Tıp; Üroloji ve Nefroloji; Farmakoloji ve Eczacılık; Toksikoloji